Science Generic Skills Improvement through Student Centered Learning - Siska Desy; Fatmaryanti Fatmaryanti; Sarwanto Sarwanto (Proceeding of International Conference on Islamic Education, 2016)
This study was aimed to determine the effectiveness of student centered learning (SCL) in improving science generic skills of high school students. The study was confined to the application of the 2 models based on SCL are guided inquiry model and multiple representations model. This research was quasi experiment with a control group pretest-posttest design. The study was conducted in 2 high schools in Purworejo district. The independent variable was a guided inquiry model in the first study while in the second study was multi representation model. Both studies had the same dependent variable, namely science generic skills of high school students. Results of research have shown that this two learning models are proven more effective in improving science generic skills of high school students than conventional learning model.